PHYSICAL ENVIRONMENT MEASUREMENT OF D6 CAMPUS CLASSROOMS AT GUNADARMA UNIVERSITY - Nurjannah, Nurjannah; Yuniar, Yuyun (Sustainable Environmental and Optimizing Industry Journal, 2024)
Gunadarma University is one of the leading private universities in Indonesia. In order to support the existing teaching and learning process, a comfortable and safe classroom is needed so that the learning and teaching process runs efficiently and effectively. Classrooms are one of the infrastructures that determine the success of the teaching and learning process. One of the Gunadarma University buildings used in the teaching and learning process is the D6 campus located on the margonda raya road which consists of 6 floors, this research is focused on measuring one of the classrooms, namely D655 on the 5th floor. D6 campus is one of the oldest campuses and has just finished renovating its classrooms, so it is the object of this research. The purpose of this study is to measure the physical environment of the classroom related to temperature and humidity, lighting levels and classroom noise used for the teaching and learning process. Measurements of the physical environment of the classroom measured include room temperature and humidity, lighting and noise levels. This measurement aims to determine the condition of the physical environment of the classrooms in the D6 campus. Based on the measurements taken, the average class temperature was 24.4% with 32% humidity, the average measurement of the lighting level was 250.2 Lux, and the average measurement of the class noise level was 53.4 dBA